Identification of immune‐activating metabolite for enhancing T cell therapy of cancer. Issue 7 (18th May 2021) - Cong, Boyi; Cui, Zenghui; Cao, Xuetao
Abstract : In this Research Highlight, we summarized the results from a study by Wu et al . published in Nature Cell Biology which uncovered that asparagine (Asn), a non‐essential amino acid in mammalians, is able to enhance the TCR‐mediated activation and efficacy of CD8 + T cells towards tumour through lymphocyte‐specific protein tyrosine kinase (LCK) signalling. This study provides insights into the physiological function of Asn in T cell activation and effector functions, showing the encouraging possibility of key metabolites for empowering cancer immunotherapy.